Pengaruh Book Tax Differences, Fee Audit dan Keandalan Akrual terhadap Persistensi Laba Perusahaan Indeks KOMPAS100 - Gede Oka Restu Pratama; I Made Pradana Adiputra; Putu Yunartha Pradnyana Putra (Jurnal Widya Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of book tax differences, audit fees, and accrual reliability on earnings persistence in companies included in the KOMPAS100 Index for the period 2020-2023. Persisten earnings refelct the quality of financial performance and serve as a relevant predictor of future earnings for economic decision-makers. This research employs a quantitative approach with an associative method. The sample was selected using purposive sampling resulting in 19 companies and a total of 76 annual observations. Data were obtained from annual financial statements published on the official website of the Indonesia Stock Exchange. The analysis was conducted using multiple linear regression to examine the effect of the independent variables on earnings persistence, with the assistance of SPSS version 26 for Windows. The results indicate that (1) book tax differences have a negative and significant partial effect on earnings persistence, (2) audit fees have no significant partial effect on earnings persistence, and (3) accrual reliability has a positive and significant partial effect on earnings persistence.